Synthesis and mode transformation analysis of double loop 7R mechanism with motion and locking modes - Wei Liu; Nan Zhang; Binbin Meng (Advances in Mechanical Engineering)
Analyzing the different characteristics of tangent lines of the coupler point curve of 4R mechanism, a 3R kinematic chain in a singular configuration is set up, planar and spherical 7R mechanisms with motion and locking modes are synthesized. Based on the spherical 4R mechanism with threefold and quadruple points on the coupler point curve, a spherical 7R mechanism with multiple motion and locking mode is ã synthesized. By analyzing the spherical 7R mechanism using screw theory, the motion mode transformation configuration of the mechanism when the coupler point curve of the spherical 4R loop is at a cusp are analyzed. The results show that this type of 7R mechanism can achieve the transformation of motion and locking modes. By changing the configuration of the singular 3R kinematic chain, the motion mode of the 4R mechanism loop under different motion bifurcation configurations can be transformed. The proposed method also has certain application value in designing, analyzing, and optimizing multi-mode mechanisms that meet the transformation requirements of motion and locking production operations.